Experimental investigation on the construction waste recycled sand reinforced by soybean urease-induced calcium carbonate precipitation - Huang, Junyi; Wu, Dazhi; Wang, Zhe; Lu, Nan; Liu, Shu; Zhou, Pan (Frontiers in Earth Science, 2025)
Recycled sand from construction waste presents a promising substitute for natural sand. However, such sand typically exhibits low strength, high crushing index, and poor grading, which collectively compromise its performance in subgrade applications subjected to cyclic shear stresses caused by wave, seismic, and traffic loads. This study investigates the application of Soybean Urease-Induced Calcium Carbonate Precipitation (SICP) method to enhance the engineering properties of recycled sands. Firstly, several factors influencing the precipitation process are examined, including soybean powder concentration, cementation solution concentration and the ratio between urea and calcium chloride. Subsequently, unconfined compressive tests are conducted on sands reinforced under various conditions. Results indicate that the sample strength increases significantly with higher cementation solution concentration and grouting frequency; however, excessively high concentrations lead to a decline in sample strength, likely due to the reduced calcium carbonate precipitation efficiency under supersaturated conditions. Scanning electron microscopy reveals that the reinforcing effect can be attributed to calcium carbonate crystals formed between particles, which function as binding agents for the recycled sands.